Physicochemical Properties of Single Cell Oil Extracted from Oleaginous Yeasts (University of Khartoum Journal of Agricultural Sciences, 2022)
The study aimed at extracting single cell oil (SCO) from some oleaginous yeasts living on wheat straw and sugarcane molasses media and to determine physicochemical properties of the produced oil for further assessment as edible oil. Thirty samples of yeasts were isolated according to the different methods based on the source of isolates. The effectiveness of oleaginous yeast to produce the single cell oil was studied, when the yeast was grown on two types of wheat straw media (detoxified liquid hydrolysate (DLH) and non-detoxified liquid hydrolysate (NDLH)), and molasse media. Single cell oil was extracted by hexane. Saccharomyces cerevisiae and Pichia guilliermondii were used to produce SCO. SCO produced from oleaginous yeasts in sugarcane molasses media was significantly (P≤0.05)   higher than that produced in wheat straw media. DLH of wheat straw gave higher productivity of oil than NDLH wheat straw. Generally, S. cerevisiae gave higher oil productivity (84 %), compared to P. guilliermondii (52 %).The results indicated that most of the physicochemical properties of extracted oil were found to be within the recommended limit of the common edible oil reported, except for the iron content; it ranged from 21 to 24 mg/kg, which was 4-5 times more than the permissible level of that of the Codex Alimentarius Commission. In addition, single cell oil produced by molasses contained omega-3 fatty acids such as eicosapentaenoic and docosahexaenoic which are not found in vegetable oil. Also the unsaturated fatty acids of SCO produced in wheat straw media were higher than that produced in molasses media. The fatty acid profile of SCO produced in molasses media was different from that of vegetable oils. The good physicochemical characteristics and fatty acids profile of SCO from wheat straw make it safe and a promising potential raw material for production of edible oil. The result of this study suggests the isolation of oleaginous yeast in order to be used in the edible oil production
Keywords: Oleaginous yeast; Saccharomyces cerevisiae; single cell oil; physicochemical properties; Pichia guilliermondii